Flaky zirconium oxide powder for coating and preparation method thereof
By using a combination method of deionized water, dispersant and ethanol solution in the preparation of zirconia, pure monoclinic flake zirconia was successfully prepared, solving the problem of difficulty in mass production and application in the prior art, and achieving a zirconia powder for coatings with simple process, low cost and excellent performance.
Patent Information
- Application Number
- CN202411479112.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
It is difficult to mass produce pure monoclinic zirconia in the prior art, and its application in coatings has not been reported.
Deionized water is used as the bottom water, and after adding dispersant, the alkali and zirconium liquid are titrated at a certain flow rate ratio, and hydrolysis experiments are carried out, and evaporated and grown in a vacuum electron beam furnace. Then, ethanol solution is added to the powder for infiltration and stirring, and dried naturally to obtain pure monoclinic flake zirconia.
It has achieved simple process, low cost and uniform dispersion of pure monoclinic zirconia preparation, broadening its application market in the field of organic polymer material reinforcement such as coatings.
Smart Images

Figure CN118993140B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of zirconium oxide powder preparation, and in particular to a flaky zirconium oxide powder for coatings and a preparation method thereof. Background Art
[0002] ZrO2 is an oxide ceramic material with good physical and chemical properties. It has a high melting point, low thermal conductivity, thermal expansion coefficient similar to that of metal materials, and strong corrosion resistance. It uses the principle of phase change toughening to make ceramics toughened with excellent high-temperature strength and toughness and special crystal structure. Its excellent properties make it widely used in various ceramic materials such as structural ceramics, functional ceramics, bioceramics, etc. Nanostructured materials, such as nanowires, nanorods, and nanosheets, show new physical properties and have potential applications in many fields. With the continuous expansion of the application of ZrO2 in the field of high technology, the preparation of zirconium oxide particles with different morphologies has become another hot spot in ZrO2 research. After adding flaky materials (such as graphite) to the matrix material, they can have toughening mechanisms such as microcracks, crack deflection, bridging, and particle extraction. If ZrO2 has a flaky structure, it has both phase change toughening and the toughening effect of flaky particles, which will better improve the strength and toughness of ceramics.
[0003] According to the relevant literature, there are only a few hydrothermal and water quenching methods for preparing flaky zirconia. Liu Jianmin et al. prepared flaky zirconia by hydrothermal method (a method for preparing flaky partially stabilized zirconia, patent application number: 201810740824.0). This method uses hydrothermal method to obtain flaky zirconia. The disadvantage is that it involves high temperature and high pressure hydrothermal kettle, which has strict requirements on equipment, and the hydrothermal generation is tetragonal or cubic zirconia, not pure monoclinic zirconia. Meng Fantao et al. prepared flaky zirconia by water quenching method (synthesis of flaky nano-zirconia by water quenching method, patent application number: 201410096973.X), mixed 70-90% zirconium boride and 10-30% silicon carbide by volume, added to anhydrous ethanol, ball milled and dried, and hot pressed and sintered in argon atmosphere to prepare zirconium boride-silicon carbide ceramics. The surface of the zirconium boride-silicon carbide ceramic is then polished, and then heated to 900-1100°C for 0.2-1.0h. The water quenching solution temperature is 10-30°C, and the solution is dried after water quenching. The process is repeated 0-2 times to generate flaky nano zirconium oxide particles on the surface of the zirconium boride-silicon carbide ceramic. The disadvantage of this method is that the sample yield is too low, and it is impossible to mass produce the product. Moreover, tetragonal or cubic zirconium oxide is generated, not pure monoclinic zirconium oxide. Moreover, the application of flaky nano zirconium oxide in coatings has not been reported. The flaky zirconium oxide obtained by the present invention is pure monoclinic zirconium oxide. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the present invention provides a flaky zirconium oxide powder for coatings and a preparation method thereof. The present invention has a simple process, low cost, uniform dispersion, and tests on the crystal phase, morphology, pencil hardness and glossiness of the coating after adding the flaky zirconium oxide powder, with good results. The obtained flaky zirconium oxide has a large application market in the field of reinforcing organic polymer materials such as coatings.
[0005] The invention provides a method for preparing flaky zirconium oxide powder for coatings, which comprises the following steps: using deionized water as base water, adding a dispersant and stirring, titrating an alkali solution and a zirconium solution into the base water according to a certain flow rate ratio to an end point pH, performing a hydrolysis experiment on the obtained slurry, washing with deionized water and filtering several times to obtain a filter cake, and evaporating and directionally growing the filter cake in a vacuum electron beam furnace to obtain a powder, then adding an ethanol solution to the powder for infiltration and stirring, and drying naturally to obtain the flaky zirconium oxide;
[0006] Wherein, the alkali solution is a sodium hydroxide solution with a concentration of 2.0-4.8 mol / L and a mass fraction of ≥96.00%, the concentration of the zirconium liquid is 0.01-0.05 mol / L, the flow rate ratio is (10-15):24; the hydrolysis temperature is 80-150°C, and the time is 60-100h; the temperature in the vacuum electron beam furnace is 700-900°C.
[0007] Preferably, the dispersant is polyacrylic acid, pH=4.
[0008] Preferably, the zirconium liquid is one or more of zirconium oxychloride or zirconium chloride solution.
[0009] Preferably, the ethanol solution is a 95% ethanol aqueous solution.
[0010] Preferably, the mass ratio of the ethanol solution to the powder is 1:(10-12), and the wetting and stirring time is 15-25 min.
[0011] Preferably, the endpoint pH value is 8-11.
[0012] Preferably, the hydrolysis temperature is 80-120°C.
[0013] Preferably, the temperature in the vacuum electron beam furnace is 700-800°C.
[0014] The present invention also provides a flaky zirconium oxide powder for coating prepared by the above method.
[0015] Beneficial effects of the present invention:
[0016] The present invention can well control the directional growth of the crystal surface by combining a chemical method (hydrolysis method) with a physical method (vacuum electron beam), and add ethanol to the powder to reduce agglomeration, and finally obtain pure monoclinic flaky zirconium oxide. The hydrolysis method does not involve high temperature and high pressure, is safe and reliable, has a simple process, a short preparation cycle, and can be mass-produced to save costs;
[0017] The invention obtains pure monoclinic flaky zirconium oxide, which improves the optical properties of the coating to a certain extent when added to the coating, has a large application market in the field of reinforcing organic polymer materials such as coatings, and broadens the application range of zirconium oxide powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a SEM image of zirconium oxide in Example 1;
[0019] Figure 2 is a SEM image of zirconium oxide in Example 2;
[0020] Figure 3 is a SEM image of zirconium oxide in Example 3;
[0021] Figure 4 is a SEM image of zirconium oxide in Example 4;
[0022] Figure 5 is the SEM image of zirconium oxide in Reference Example 1;
[0023] Figure 6 is the SEM image of zirconium oxide in Reference Example 2;
[0024] Figure 7 XRD patterns of zirconium oxide in Examples 1-4 and Reference Examples 1-2 (from top to bottom);
[0025] Figure 8 is a SEM image of zirconium oxide A1-1 in Example 1;
[0026] Fig. 9 is a SEM image of zirconium oxide B1-1 in Example 1;
[0027] Fig.10 is a SEM image of zirconium oxide C1-1 in Example 1;
[0028] Fig.11 This is the SEM image of zirconium oxide D1-1 in Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further explained below by examples, but the protection scope of the present invention is not limited in any form by the examples.
[0030] The present invention tests the crystal phase, morphology, pencil hardness and glossiness of the coating after adding the flaky zirconium oxide powder. The crystal phase is measured by an X-ray diffractometer; the morphology is measured by a scanning electron microscope; the pencil hardness of the coating is measured by a Mitsubishi pencil; and the glossiness of the coating is measured by a gloss meter.
[0031] Example 1
[0032] 100mL of deionized water was used as the base water, and 1.0mL of polyacrylic acid with pH=4 was added. After stirring, 0.03mol / L zirconium oxychloride solution and 3.5mol / L sodium hydroxide were titrated into the base aqueous solution at a flow rate ratio of 15:23, until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment with a set temperature of 100°C and a time of 120h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was no longer white in the silver nitrate solution. The filter cake was then evaporated and directionally grown in a 700°C vacuum electron beam furnace to obtain zirconium oxide powder, which was then infiltrated and stirred with 95% ethanol solution: powder at a mass ratio of 1:10, and dried naturally to obtain flaky zirconium oxide A1. The morphology and crystal phase of A1 were measured, and the aspect ratio was about 15:1.
[0033] Different flow rate ratios result in different slurry states and different particle sizes. In this embodiment, the flow rate ratio was adjusted, and the flake zirconium oxide A1-1 and A1-2 were also studied. The conditions and results are shown in Table 1:
[0034] Table 1
[0035] ,
[0036] The powders obtained under different hydrolysis conditions are also different. In this example, the hydrolysis temperature was adjusted, and the flake zirconium oxide B1-1 and B1-2 were also studied. The conditions and results are shown in Table 2:
[0037] Table 2
[0038] ,
[0039] The powders obtained under different hydrolysis conditions are also different. In this example, the hydrolysis time was adjusted, and the flake zirconium oxide C1-1 and C1-2 were also studied. The conditions and results are shown in Table 3:
[0040] Table 3
[0041] ,
[0042] The powders obtained with different alkali solution concentrations are also different. In this example, the concentration of the sodium hydroxide solution was adjusted, and the flake zirconium oxide D1-1 and D1-2 were also studied. The conditions and results are shown in Table 4:
[0043] Table 4
[0044] ,
[0045] Preparation of coating layer: Mullite, silicon carbide and aluminum nitride are mixed in a mass ratio of 20:1:1, ball milled to obtain a mixed powder, and then flaky zirconium oxide powder A1 is added as a reinforcing agent and aluminate cement, asphalt, limestone powder, polycarboxylate water reducer and deionized water (mass ratio = 1:10:0.3:0.1:1:50) are ball milled to obtain a precursor; the precursor is evenly coated on the metal surface, placed in an oven for drying to obtain a blank, and the blank is placed in a muffle furnace for heat treatment, and cooled with the furnace temperature to obtain a coating layer. The pencil hardness of the obtained coating is 7H and the glossiness is 70°.
[0046] Example 2
[0047] 100mL of deionized water was used as the base water, and 1.0mL of polyacrylic acid was added. After stirring, 0.05mol / L zirconium oxychloride solution and 3.5mol / L sodium hydroxide solution were titrated into the bottom aqueous solution at a flow rate ratio of 15:23 until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment. The temperature was set to 120°C and the time was 120h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was not white in the silver nitrate solution. The filter cake was then evaporated and oriented in a 700°C vacuum electron beam furnace to obtain zirconium oxide powder, and then 95% ethanol solution: powder was infiltrated and stirred at a mass ratio of 1:10, and dried naturally to obtain flaky zirconium oxide A2. The morphology and crystal phase of A2 were measured, and the aspect ratio was about 12:1. A2 was then added to the coating to prepare a coating layer, and the pencil hardness of the coating was 7H and the glossiness was 60°.
[0048] Example 3
[0049] 100mL of deionized water was used as the base water, and 1.0mL of polyacrylic acid was added. After stirring, 0.03mol / L zirconium oxychloride solution and 4.8mol / L sodium hydroxide solution were titrated into the base aqueous solution at a flow rate ratio of 15:23 until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment. The temperature was set to 100°C and the time was 100h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was no longer white in the silver nitrate solution. The filter cake was then evaporated and directionally grown in a 700°C vacuum electron beam furnace to obtain zirconium oxide powder. Then, 95% ethanol solution: powder was infiltrated and stirred at a mass ratio of 1:10, and naturally dried to obtain flaky zirconium oxide A3. The morphology and crystal phase of A3 were measured, and the aspect ratio was about 12:1. A3 was then added to the coating to prepare a coating layer, and the coating had a pencil hardness of 7H and a glossiness of 65°.
[0050] Example 4
[0051] 100mL of deionized water was used as the base water, and 1.0mL of polyacrylic acid was added. After stirring, 0.05mol / L zirconium oxychloride solution and 4.8mol / L sodium hydroxide solution were titrated into the base aqueous solution at a flow rate ratio of 10:23 until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment. The temperature was set to 100°C and the time was 120h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was no longer white in the silver nitrate solution. The filter cake was then evaporated and directionally grown in a vacuum electron beam furnace at 800°C to obtain zirconium oxide powder. Then, 95% ethanol solution: powder was infiltrated and stirred at a mass ratio of 1:12, and naturally dried to obtain flaky zirconium oxide A4. The morphology and crystal phase of A4 were measured. The grain aspect ratio was about 10:1. A4 was then added to the coating to prepare a coating layer. The coating had a pencil hardness of 6H and a glossiness of 65°.
[0052] Reference example 1
[0053] 100mL of deionized water was used as the base water, and 1.0mL of polyacrylic acid was added. After stirring, 0.03mol / L zirconium oxychloride solution and 3.5mol / L sodium hydroxide solution were titrated into the base aqueous solution at a flow rate ratio of 15:23 until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment. The temperature was set to 100℃ and the time was 120h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was no longer white in the silver nitrate solution. The filter cake was then calcined in a 700℃ experimental furnace to obtain zirconium oxide powder. Then, 95% ethanol solution: powder was infiltrated and stirred at a mass ratio of 1:10, and naturally dried to obtain zirconium oxide A'1. Since the vacuum electron beam furnace changed the growth direction of the grains, the morphology and crystal phase of A'1 were measured, and the aspect ratio was about 2:1. A'1 was then added to the coating to prepare a coating layer, and the coating had a pencil hardness of 4H and a glossiness of 70°.
[0054] Reference example 2
[0055] 100mL of deionized water was used as base water, and 1.0mL of polyacrylic acid was added. After stirring, 1.0mol / L zirconium oxychloride solution and 4.8mol / L sodium hydroxide solution were titrated into the base aqueous solution at a flow rate ratio of 10:23, until the end point pH value was 9.0. The slurry was transferred to a three-necked flask for a hydrolysis experiment. The temperature was set to 100°C and the time was 120h. The obtained slurry was washed with deionized water and filtered several times until the washing liquid was no longer white in the silver nitrate solution. The filter cake was then evaporated and directionally grown in a 700°C vacuum electron beam furnace to obtain zirconium oxide powder and flaky zirconium oxide A'2. The morphology and crystal phase of A'2 were measured, and the aspect ratio was about 5:1. A'2 was then added to the coating to prepare a coating layer, and the coating had a pencil hardness of 6H and a glossiness of 45°.
[0056] Characterization example
[0057] The morphology and crystal phase of Examples 1-4 and Reference Examples 1-2 were analyzed by scanning electron microscopy (SEM) and laser diffraction (XRD), and the results were as follows: Figure 1-Figure 6 and Figure 7 As shown in Table 1, the blank sample (no zirconium oxide is added to the coating), Examples 1-4 and Reference Examples 1-2 in which flaky zirconium oxide is added to the coating to measure the physical properties of the coating, namely, pencil hardness (measured in accordance with the method specified in the national standard GB / T 6739-2006, the pencil hardness of the coating is measured by the wheelbarrow method, and the hardness of the coating when the pencil leaves a mark on the surface after scratching the coating is the pencil hardness of the coating) and glossiness (gloss meter).
[0058] Table 5 Pencil hardness and glossiness of the coating after zirconium oxide was added to the coating in different embodiments and reference examples
[0059] ,
[0060] Depend on Figure 1 It can be seen that the zirconium oxide obtained in Example 1-2 is a relatively regular flake, while the zirconium oxide obtained in Reference Example 1-2 is granular. The morphologies of the zirconium oxides obtained by the two methods are completely different. Figure 2 As shown, Examples 1-4 obtained pure monoclinic zirconium oxide, while Reference Examples 1-2 obtained tetragonal and monoclinic zirconium oxide, and the crystal phase structures of the two are completely different. As can be seen from Table 1: the zirconium oxide obtained in the Examples and Reference Examples added to the coating has a significant difference in the effects on the pencil hardness and glossiness of the coating layer, among which Examples 1-4 have improved the pencil hardness and glossiness of the coating layer to a certain extent. While the Reference Example improves one physical property, it reduces another physical property.
[0061] The object of the present invention is to provide a flaky zirconium oxide powder for coating and a preparation method thereof, which comprises: using deionized water as base water, adding a dispersant, and after stirring, titrating 2.0-4.8 mol / L alkali solution and 0.01-0.05 mol / L zirconium solution into the base water solution according to a certain flow rate ratio until the end point pH value is 8-11, transferring the slurry into a three-necked flask, and performing a hydrolysis experiment (hydrolysis temperature is 80-120°C, time is 60-100h), washing the obtained slurry with deionized water and suction filtering for several times until the washing liquid is not white in a silver nitrate solution, and then evaporating and directionally growing the filter cake in a vacuum electron beam furnace (temperature is 700-900°C) to obtain a powder, and then infiltrating and stirring an ethanol solution and the powder at a mass ratio of 1: (10-12), and drying naturally to obtain a flaky zirconium oxide. The mechanism of the present invention is that the dispersant added in the process plays the role of a surfactant, reduces the mutual adsorption of zirconium oxide powder, reduces the formation of hydroxyl bridges between particles, and also reduces the capillary force generated during the dehydration process, so that the bonding strength between particles is reduced, thereby effectively preventing the formation of hard agglomerates between particles and reducing the particle size of the powder. At the same time, the method of the present invention ensures that when the content of zirconium oxide remains unchanged, the aspect ratio of zirconium oxide grains is changed. As the aspect ratio of the grains increases to a certain extent, the pencil hardness of the prepared coating layer increases, and the glossiness of the coating is also better. When the aspect ratio of the grains is lower than 5:1, the pencil hardness and glossiness of the prepared coating layer are not ideal. The reason is that the directional adsorption of the electron beam furnace can better control the directional growth of the crystal face during calcination, and the monoclinic zirconium oxide with a sheet structure is obtained. It is then infiltrated and stirred with ethanol to reduce the mutual attraction between molecular forces and capillary forces, and the soft agglomeration between particles is conducive to dispersion added to the coating layer, thereby improving the physical properties of the coating layer.
[0062] The invention provides a flaky zirconium oxide powder for coating and a preparation method thereof, which is characterized in that: deionized water is used as base water, a dispersant is added, and after stirring, 2.0-4.8 mol / L alkali solution and 0.01-0.05 mol / L zirconium solution are titrated into the base water solution according to a certain flow rate ratio until the end point pH value is 8-11, the slurry is transferred to a three-necked flask, and a hydrolysis experiment is carried out (the hydrolysis temperature is 80-120°C, and the time is 60-100h), the obtained slurry is washed with deionized water and filtered several times until the washing liquid is not white in the silver nitrate solution, and then the filter cake is evaporated and directionally grown in a vacuum electron beam furnace (temperature is 700-900°C) to obtain powder, and then ethanol solution: powder = 1:10-12 (mass ratio) is infiltrated and stirred, and dried naturally to obtain flaky zirconium oxide. The flaky zirconium oxide powder is tested for crystal phase, morphology, pencil hardness and glossiness of the coating after adding the powder. The invention has simple process, low cost and uniform dispersion, and the obtained flaky zirconium oxide has a large application market in the field of reinforcing organic polymer materials such as coatings.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing flaky zirconium oxide powder for coating, characterized in that: Deionized water is used as the base water. After adding the dispersant and stirring, the alkali solution and the zirconium solution are titrated into the base water at a certain flow rate ratio to the end point pH. The obtained slurry is subjected to a hydrolysis experiment, washed with deionized water and filtered several times to obtain a filter cake, which is evaporated and directionally grown in a vacuum electron beam furnace to obtain a powder. Then, an ethanol solution is added to the powder for infiltration and stirring, and the powder is naturally dried to obtain flaky zirconium oxide. The alkali solution is a sodium hydroxide solution with a concentration of 2.0-4.8 mol / L, the concentration of the zirconium solution is 0.01-0.05 mol / L, the flow rate ratio is (10-15):24; the hydrolysis temperature is 80-150°C, the time is 60-100h; the temperature in the vacuum electron beam furnace is 700-900°C.
2. The preparation method according to claim 1, characterized in that: The dispersant is polyacrylic acid, pH=4.
3. The preparation method according to claim 1, characterized in that: The zirconium liquid is one or more of zirconium oxychloride and zirconium chloride solution.
4. The preparation method according to claim 1, characterized in that: The ethanol solution is a 95% ethanol aqueous solution.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the ethanol solution to the powder is 1:(10-12), and the soaking and stirring time is 15-25 minutes.
6. The preparation method according to claim 1, characterized in that: The endpoint pH value is 8-11.
7. The preparation method according to claim 1, characterized in that: The hydrolysis temperature is 80-120°C.
8. The preparation method according to claim 1, characterized in that: The temperature in the vacuum electron beam furnace is 700-800°C.
Citation Information
Patent Citations
Water quenching method for preparing flaky nanometer zirconia
CN103922398A
Method for preparing sheet partially-stabilized zirconia
CN108557879A
Preparation process for synthesizing flaky nano zirconia by precipitation
CN101830507A
Preparation process for nano zirconia powder
CN103588246A